Mitigating Human-Elephant Conflict in Southeast Asia - Kochprapa, Poldej; Savini, Chution; Ngoprasert, Dusit; Savini, Tommaso; Gale, George (Tropical Natural History, 2024)
Human-elephant conflict (HEC) poses serious threats to humans and to elephants, and while HEC in Southeast Asia is increasing, mitigation effectiveness data are lacking. Previous assessments of available mitigation options have not compared relative benefits and impacts of each on a practical level to identify which factors should be considered by local agricultural communities and/or other stakeholders when choosing among mitigation options. Understanding which mitigation approach to apply in a given context is crucial for effective mitigation planning and can aid in the development of more holistic methods. We reviewed the literature regarding the strengths and weaknesses of 14 currently applied HEC mitigation methods in Southeast Asia, considering five key factors for each mitigation option: 1) effectiveness at reducing crop damage, 2) initial start-up costs, 3) maintenance/long-term costs, 4) potential impacts on humans and 5) potential impacts on elephants. Our results suggest there are considerable tradeoffs among these five factors for any given mitigation option and that none of the available mitigation methods are simultaneously highly effective in preventing crop damage and low cost while presenting minimal impact to people and elephants. Although our metric of comparison is not comprehensive, it may offer an initial set of guidelines for decision making.